Characterization of 10-hydroxygeraniol dehydrogenase from catharanthus roseus reveals cascaded enzymatic activity in iridoid biosynthesis - Krithika, Ramakrishnan; Srivastava, Prabhakar Lal; Rani, Bajaj; Kolet, Swati P.; Chopade, Manojkumar; Soniya, Mantri; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Catharanthus roseus [L.] is a major source of the monoterpene indole alkaloids (MIAs), which are of significant interest due to their therapeutic value. These molecules are formed through an intermediate, cis-trans-nepetalactol, a cyclized product of 10-oxogeranial. One of the key enzymes involved in the biosynthesis of MIAs is an NAD(P)(+) dependent oxidoreductase system, 10-hydroxygeraniol dehydrogenase (Cr10HGO), which catalyses the formation of 10-oxogeranial from 10-hydroxygeraniol via 10-oxogeraniol or 10-hydroxygeranial. This work describes the cloning and functional characterization of Cr10HGO from C. roseus and its role in the iridoid biosynthesis. Substrate specificity studies indicated that, Cr10HGO has good activity on substrates such as 10-hydroxygeraniol, 10-oxogeraniol or 10-hydroxygeranial over monohydroxy linear terpene derivatives. Further it was observed that incubation of 10-hydroxygeraniol with Cr10HGO and iridoid synthase (CrIDS) in the presence of NADP(+) yielded a major metabolite, which was characterized as (1R, 4aS, 7S, 7aR)-nepetalactol by comparing its retention time, mass fragmentation pattern, and co-injection studies with that of the synthesized compound. These results indicate that there is concerted activity of Cr10HGO with iridoid synthase in the formation of (1R, 4aS, 7S, 7aR)-nepetalactol, an important intermediate in iridoid biosynthesis.